Kelios pastabos dėl formų šų̃, sesų̃ - Vitkauskas, Vytautas (Baltistica, 1966)
Some notes about forms šų̃, sesų̃The short lingual analysis of žemaičiai dialects noun consonantial stem forms šų̃, sesų̃ allowed us to draw the conclusion that these forms apeared as a result of wrong transponated forms šu·n, sesu·n of žemaičiai dūnininkai (Var̃niai, Pãvandenė, Váiguva) in the literature language. It happened in this way when the consonant n apeared as a result of the latter nasalisation of vowels i, u which descended from diphthongs ie, uo in these dialects.
Keywords: žemaičių tarmė; morfologija; priebalsinio kamieno formos